Why The Sky Is Blue: The Ozone Connection Revisited - Raghuprasad, Puthalath Koroth (European Journal of Applied Sciences, 2022)
Blue sky is a feature on earth and Mars, the only planets in our solar system with well-defined layer(s) of ozone in their atmospheres. After heavy rains remove most of the dust and varying amounts of gases, the earth’s sky appears deeper blue; this argues against Rayleigh’s scattering as being responsible for the blue color of sky. Also, in this paper we make the argument that since at least 50% of earth’s atmospheric molecules are held close to the surface of the earth, in the lower 6 km or so, Rayleigh scattering should make the sky closer to the earth appear deeper blue and the overhead sky lighter; in fact, the reverse is true. We also believe that scattering of blues in all directions should make the clouds and the objects close to the ground also to take on the blue color; instead, what we see is white clouds floating in front of a uniform background of blue and no increase in blue tinge in the structures close to the earth’s surface. In contrast, the true splitting of setting sun’s rays makes the light and the sky to take on an orange-red color, but in this setting the clouds and objects in the rays’ path also appear yellow-orange, as one would expect. The absence of blue sky in other planets’ and our moon’s skies despite having varying mixtures of gases but no defined ozone layer, and the black “sky” beyond the lower parts of the earth’s atmosphere beyond the stratosphere, and particularly the appearance of a sharp demarcation about the lower part of the stratosphere where the blue stops and black sky appears, all argue in favor of ozone as being responsible for the blue color of sky. We propose in this paper that the proper color of sky is dark blue, as seen in pristine locations and in photographs of the earth from space, but the sky over cities and other dusty places becomes lighter blue; the almost white color of sky at horizon is due to the density of dust in the atmosphere closest to the ground.